2018
DOI: 10.1021/acschemneuro.8b00620
|View full text |Cite
|
Sign up to set email alerts
|

CoREST Complex-Selective Histone Deacetylase Inhibitors Show Prosynaptic Effects and an Improved Safety Profile To Enable Treatment of Synaptopathies

Abstract: Synaptic dysfunction is a pathological feature in many neurodegenerative disorders, including Alzheimer’s disease, and synaptic loss correlates closely with cognitive decline. Histone deacetylases (HDACs) are involved in chromatin remodeling and gene expression and have been shown to regulate synaptogenesis and synaptic plasticity, thus providing an attractive drug discovery target for promoting synaptic growth and function. To date, HDAC inhibitor compounds with prosynaptic effects are plagued by known HDAC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 53 publications
(136 reference statements)
6
39
0
Order By: Relevance
“…126 In addition, modifications at the ZBG of a hydroxamic acid, which is the most common ZBG employed for the development of HDACis, 127 to an orthoaminoanilide moiety can lead to selective inhibition of HDAC1, 2, and 3, 55,127 while additional modifications in this ZBG through the insertion of heteroaromatic rings can result in the exploitation of additional interactions with an internal cavity, known as the foot pocket ( Figure 3A), 83,84 present in the structure of HDAC1 and 2, and, consequently, trigger selective inhibition of these two isoforms over HDAC3. 55 It is important to highlight that the kinetics related to the binding of the hydroxamic acid and ortho-aminoanilide moiety to Zn 2+ are different, in which the ortho-aminoanilide have a highest residence time in the active site. 84 It has been shown that the selective inhibition of class IIa (HDAC4, 5, 7, and 9) can also be achieved through an exploration of a selectivity cavity on the surface of these isoforms adjacent to the zinc channel, which is specific for this HDAC subfamily.…”
Section: Pharmacophoric Features Of Hdacismentioning
confidence: 99%
See 2 more Smart Citations
“…126 In addition, modifications at the ZBG of a hydroxamic acid, which is the most common ZBG employed for the development of HDACis, 127 to an orthoaminoanilide moiety can lead to selective inhibition of HDAC1, 2, and 3, 55,127 while additional modifications in this ZBG through the insertion of heteroaromatic rings can result in the exploitation of additional interactions with an internal cavity, known as the foot pocket ( Figure 3A), 83,84 present in the structure of HDAC1 and 2, and, consequently, trigger selective inhibition of these two isoforms over HDAC3. 55 It is important to highlight that the kinetics related to the binding of the hydroxamic acid and ortho-aminoanilide moiety to Zn 2+ are different, in which the ortho-aminoanilide have a highest residence time in the active site. 84 It has been shown that the selective inhibition of class IIa (HDAC4, 5, 7, and 9) can also be achieved through an exploration of a selectivity cavity on the surface of these isoforms adjacent to the zinc channel, which is specific for this HDAC subfamily.…”
Section: Pharmacophoric Features Of Hdacismentioning
confidence: 99%
“…54,144 The diamino-aniline core of CI-994 (3) and Cpd-60 (8) was replaced by a diamino-heterocycle group in Rodin-A (9), maintaining the Zn +2 -chelating capacity and occupying the "foot pocket" at the same time ( Figure 7). 55 Cpd-60 (8) is more potent in inhibiting class I HDACs (HDAC1, HDAC2, and HDAC3) than Rodin-A (9), but similar to CI-994 (3), it displays hematological toxicity, causing severe toxic effects on myeloid and erythroid progenitor cells. Rodin-A (9) has been shown to minimize hematological side effects, and it has a similar IC 50 profile on the CoREST complex, HDAC1 and HDAC2 when compared with CI-994 (3).…”
Section: Case Studies Of Hdac Inhibition Associated With Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual-hybrid agent has been successfully used as a potential therapeutic in cancer studies by reducing the proliferation of mouse melanoma cells through blocking the active sites of HDAC1 and LSD1 of the LCH complex (Kalin et al, 2018). Synaptic dysfunction is a common in many neurodegenerative diseases including AD, with HDACs involved in regulating synaptogenesis and synaptic plasticity (Fuller et al, 2019). HDAC inhibitors have been trialed to improve synaptic growth and function, but have been limited due to their off-target effects and dose-limiting hematologic toxicities.…”
Section: The Corest Complex As a Potential Target For Therapeuticsmentioning
confidence: 99%
“…HDAC inhibitors have been trialed to improve synaptic growth and function, but have been limited due to their off-target effects and dose-limiting hematologic toxicities. Fuller et al (2019) used the CoREST-selective HDAC inhibitor Rodin-A in a mouse model and were successful in increasing spine density, expression of synaptic proteins and long-term potentiation at suitable doses to allow for chronic treatment. This study has shown that selectively targeting the CoREST complex, and not the Sin3, NCoR, and NuRD complexes, offers a promising therapeutic for synaptopathies and that the CoREST complex is a key regulator of synaptic growth and function (Fuller et al, 2019).…”
Section: The Corest Complex As a Potential Target For Therapeuticsmentioning
confidence: 99%